Susceptibility to renal carcinoma in the Eker rat involves a tumor suppressor gene on chromosome 10. - Yeung, R S (1993)
Germ-line mutations of tumor suppressor genes confer strong predisposition to tumor formation. In the rat, a form of dominantly inherited renal carcinoma (RC) results in multiple chromophobe cell tumors that resemble the human disease, and heterozygous carriers (RC/+) are highly susceptible to environmental agents (radiation and chemical carcinogens), making it a desirable model to study epithelial carcinogenesis. By linkage analysis, the locus of the inherited RC mutation was mapped to rat chromosomal band 10q12, near the protamine locus (logarithm of odds score = 17.96). Renal tumors also showed a loss of heterozygosity at this locus, lending support to the recessive nature of this putative tumor suppressor gene. Our result suggested that the human homolog of the RC gene may reside on human chromosome 16, not known to be altered commonly in human RC.